2021
DOI: 10.7717/peerj.11491
|View full text |Cite
|
Sign up to set email alerts
|

Using a mobile health app to improve patients’ adherence to hypertension treatment: a non-randomized clinical trial

Abstract: Poor adherence to hypertension treatment increases complications of the disease and is characterized by a lack of awareness and acceptance of ongoing treatment. Mobile health (mHealth) apps can optimize processes and facilitate access to health information by combining treatment methods with attractive solutions. In this study, we aimed at verifying the influence of using an mHealth app on patients’ adherence to hypertension treatment, also examining how user experience toward the app influenced the outcomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 59 publications
1
26
0
1
Order By: Relevance
“…The analysis showed that studies on the use of mobile applications were conducted in the USA (n=7) ( 30 - 36 ), Sweden (n=3) ( 37 - 39 ), Republic of Korea (n=1) ( 40 ), Brazil (n=1) ( 41 ), Norway (n=2) ( 42 , 43 ), Switzerland (n=1) ( 44 ), Belgium (n=1) ( 45 ), China (n=9) ( 22 , 46 - 53 ), Romania (n=1) ( 54 ), Japan (n=1) ( 55 ), Finland (n=1) ( 24 ), France (n=1) ( 56 ), New Zealand (n=1) ( 57 ), Iran (n=2) ( 58 , 59 ), Georgia (n=1) ( 60 ), Spain (n=2) ( 61 , 62 ), Palestine (n=1) ( 63 ) and Germany (n=3) ( 64 - 66 ). Two studies were conducted simultaneously in India (n=2) ( 67 , 68 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis showed that studies on the use of mobile applications were conducted in the USA (n=7) ( 30 - 36 ), Sweden (n=3) ( 37 - 39 ), Republic of Korea (n=1) ( 40 ), Brazil (n=1) ( 41 ), Norway (n=2) ( 42 , 43 ), Switzerland (n=1) ( 44 ), Belgium (n=1) ( 45 ), China (n=9) ( 22 , 46 - 53 ), Romania (n=1) ( 54 ), Japan (n=1) ( 55 ), Finland (n=1) ( 24 ), France (n=1) ( 56 ), New Zealand (n=1) ( 57 ), Iran (n=2) ( 58 , 59 ), Georgia (n=1) ( 60 ), Spain (n=2) ( 61 , 62 ), Palestine (n=1) ( 63 ) and Germany (n=3) ( 64 - 66 ). Two studies were conducted simultaneously in India (n=2) ( 67 , 68 ).…”
Section: Resultsmentioning
confidence: 99%
“…By category, the research was focused on the following areas: mobile applications for diagnostic purposes (for example, ECG recording ( 30 ), assessment of heart rate ( 31 , 33 , 44 , 65 ). Some studies were carried out to validate the system for urgent care alarm ( 37 ), lifestyle changes ( 43 , 45 , 53 , 62 , 65 ), adherence to treatment ( 35 , 38 , 41 , 47 , 48 , 51 , 53 , 55 , 59 , 60 , 63 , 64 , 67 , 68 ), and physical activity of the patients ( 22 , 32 , 34 , 41 , 45 , 62 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, because higher levels of app usage were reported to be associated with increased intervention efficacy, 37 some participants in the present study may have improved their own health management through the use of the app, which improved their adherence to treatment. 38 …”
Section: Discussionmentioning
confidence: 99%
“…Many research indicated that patients using the mHealth app have bettermanaged hypertension when compared to the control group (Debon et al, 2020). Thus the mHealth app should provide a userfriendly experience to patients to maximize their involvement in managing hypertension (Volpi et al,2021).…”
Section: Introductionmentioning
confidence: 99%